Studies on financing agrarian reform in Latin America - Domike, Arthur L.; Shearer, Eric B. ([Madison, Land Tenure Center, University of Wisconsin-Madison], 1973)
This book is on the studies of financing Agarian in Latin American. It was originally issued by FAO under series number ESH: TF/LAT. 424, June 1973.
Bibliography: p. 106-121.
oo 09/04/2019
Loans
Keywords: Land reform